Prostate cancer incidence in orchidectomised male‐to‐female transsexual persons treated with oestrogens. (12th December 2013) - Gooren, L.; Morgentaler, A.
Summary Male‐to‐female transsexual persons (MtoF) undergo treatment with antiandrogens and oestrogens followed by bilateral orchiectomy. The aim of this study was to investigate the incidence of prostate cancer (PCa) in a cohort of MtoF individuals. Medical records 2306 MtoF treated between 1975 and 2006 of the Amsterdam Gender Clinic were reviewed. Mean age at initiation of treatment was 29.3 ± 12.7 years (range 16–83). Mean follow‐up was 21.4 years, resulting in a combined total of 51 173 person‐years of exposure and follow‐up. Follow‐up more than 20 years was available for 303 individuals, including follow‐up of more than 30 years in 151 individuals. A single case of PCa was identified in this group. The overall incidence of PCa in this population was 0.04% and 0.13% for individuals who had initiated hormonal treatment after at 40 years or later. PCa in this large MtoF population was rare. However, underdiagnosis is likely due to lack of close prostate monitoring and suppression of PSA due to androgen deprivation. In addition, only a limited number of MtoF individuals have yet reached old age when PCa becomes more common. When diagnosed in this population, there appears to be a tendency for PCa to behave aggressively. Prostate monitoring should be considered in these individuals beginning at age 50 years.